Criminal Responsibility of Influencers for Illegal Crypto Pump and Dump Schemes Under Indonesian Law - Yehezkiel Marbun; Rospita A Siregar (LP2M IAIN Palopo, 2026)
This study aims to analyze the criminal liability of influencers in illegal crypto asset pump-and-dump schemes following the transition of oversight to the Financial Services Authority (OJK). Using a normative judicial method, it evaluates the synchronization between the EIT Law, the National Penal Code (Law No. 1/2023), and the P2SK Law. The results indicate that influencers can be held criminally liable under Article 28, paragraph (1) of the EIT Law for disseminating misleading information that causes material loss. Simultaneously, they may be prosecuted under Article 492 of the National Penal Code for fraud. The legal standing of influencers is constructed as